Neither a multi-ingredient pre-workout supplement nor caffeine were effective at improving markers of blood flow or upper-body resistance exercise performance - Blake, M. S.; Johnson, N. R.; Trautman, K. A.; Grier, J. W.; Stastny, S.; Hackney, K. (International Journal of Exercise Science, 2020)
Few studies have measured the effects of multi-ingredient pre-workout supplements on blood flow or heart rate variability or have compared a multi-ingredient pre-workout supplement to a matched single ingredient. This study examined the effects of a multi-ingredient pre-workout supplement, an equivalent amount of caffeine, and placebo on markers of resistance training performance, blood flow, blood pressure, and heart rate variability. The study utilized a randomized, placebo-controlled, repeated-measures, crossover design. Twelve resistance-trained males (22.75 ± 4.51 yrs; 183.4 ± 7.37 cm; 91.05 ± 17.77 kg) completed the study. Resistance exercise performance was defined as total work performed during elbow flexion and extension on an isokinetic dynamometer. Blood flow was calculated using time-averaged mean velocity and blood vessel diameter of the right brachial artery, which were measured via Doppler ultrasound. Heart rate was recorded using an electrocardiogram. Neither a multi-ingredient pre-workout supplement nor caffeine alone improved upper-body resistance exercise performance or markers of blood flow relative to placebo. No differences in heart rate variability were observed across treatments. A multi-ingredient pre-workout supplement was not effective at improving performance or blood flow and did not alter autonomic nervous system function.